Beispiel Nr: 13
$ \text{Gegeben:} ax^{2}+bx+c=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ ax^{2}+bx+c=0 \\ \textbf{Gegeben:} \\ x^2+2x-24 =0 \\ \\ \textbf{Rechnung:} \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ 1x^{2}+2x-24 =0 \\ x_{1/2}=\displaystyle\frac{-2 \pm\sqrt{2^{2}-4\cdot 1 \cdot \left(-24\right)}}{2\cdot1} \\ x_{1/2}=\displaystyle \frac{-2 \pm\sqrt{100}}{2} \\ x_{1/2}=\displaystyle \frac{-2 \pm10}{2} \\ x_{1}=\displaystyle \frac{-2 +10}{2} \qquad x_{2}=\displaystyle \frac{-2 -10}{2} \\ x_{1}=4 \qquad x_{2}=-6 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ \\ x^{2}+2x-24 =0 \\ x_{1/2}=\displaystyle -\frac{2}{2}\pm\sqrt{\left(\frac{2}{2}\right)^2- \left(-24\right)} \\ x_{1/2}=\displaystyle -1\pm\sqrt{25} \\ x_{1/2}=\displaystyle -1\pm5 \\ x_{1}=4 \qquad x_{2}=-6 \end{array}\\ \end{array}$